The Indian History of an American Institution Native Americans and Dartmouth - Calloway, Colin G. (Dartmouth College Press, 2010)
A history of the complex relationship between a school and a people Dartmouth College began life as an Indian school, a pretense that has since been abandoned. Still, the institution has a unique, if complicated, relationship with Native Americans and their history. Beginning with Samson Occom's role as the first "development officer" of the college, Colin G. Calloway tells the entire, complex story of Dartmouth's historical and ongoing relationship with Native Americans. Calloway recounts the struggles and achievements of Indian attendees and the history of Dartmouth alumni's involvements with American Indian affairs. He also covers more recent developments, such as the mascot controversies, the emergence of an active Native American student organization, and the partial fulfillment of a promise deferred. This is a fascinating picture of an elite American institution and its troubled relationship- at times compassionate, at times conflicted-with Indians and Native American culture.